KONTROVERSI ZAKAT PROFESI PESRPEKTIF ULAMA KONTEMPORER - Riyadi, Fuad (UIN Sunan Kudus, 2015)
Zakat is one of five major pillars to strengthen the Islamic religion. As a way to worship Allah it has some uniqueness as a worshiping that relates mankind to their God and also mankind to others in term of social responsibility that could be assumed as a religion tax. On today’s’ development of zakat Professional zakat appears on its controversies and potential power to an economy as whole. Professional zakat seems to be a good tool that classified into a source of zakat. For its founder professional zakat is derived from the figuration of agricultural zakat; due to its new existence, it comes with tough debate and controversies among some ulama’. This writing tries to examine some controversial element of professional zakat and how it finally becomes one of potential source of zakat in Indonesia that will also influence national’s economy by several mechanisms. In the end of the writing there will a compiled figure that project the contribution of zakat for Indonesian economy.